Kaitan antara karakteristik pantai Provinsi Sumatera Barat dengan potensi kerawanan tsunami - Yudhicara, Yudhicara (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no2.20084The coast of West Sumatera Province has two types of beaches: low lying sandy beach and steep rocky beach. Straight shoreline beaches at Padang beach until Air Bangis at the north and between Pasir Ganting and Salido beach at the south will have a potential tsunami height lower than bay shape beaches like at Kasai Bay, Kabung Bay, Batung Bay and Nibung Bay. A tsunami inundation will be further at a low lying area (low lying sandy beaches) compared with a coastal area which has steep slope and high relief (steep rocky beaches). Gosong beach at Pariaman which has a steep angle of beach slope will have lower tsunami height compared with a low angle beach slope like at Sungai Beramas, Kasai, Kabung, Batung and Nibung bays which have a beach slope about 3° to 5°. The maximum tsunami inundation is assumed to be located at Pasaman and Pasir Pariaman Sub-regencies, while the maximum tsunami height is assumed to be located at the middle of mapped area which has a bay shape. Tsunami is assumed to be arrived early at the southern most of mapped area or close to Muko-muko (Bengkulu). The maximum height difference from sea level was found at Tabai - Pariaman about 5.394 m, while the minimum height difference was found at Carocok Anau about 1.821 m. The horizontal distance measured from the nearest building from the shoreline is about 119 to 173 m. The worst case of tsunami modeling assumed that the maximum tsunami height will be about 32 m and used for reference to make tsunami prone zonation, such as high, moderate and low prone area.